A gun drill mechanics model analysis based on 15-5PH solid solution stainless steel. Issue 2 (4th March 2019) - Li, Liang; He, Ning; Wu, Peng; Yang, Yinfei; Hao, Xiuqing
Abstract: Referencing special energy model, a new gun drill mechanics model was established and the influence of the cutting parameters on axial force and torque was based on 15-5PH solid solution stainless steel through theoretical analysis and cutting tests. On the basis of the existing model, the model coefficients were modified under various cutting conditions and the integral area of the cutting edge was enlarged. The eccentricity at the bottom of the drill groove was taken into account in the integral area of the cutting edge. In the meanwhile, the torque calculation was simplified reasonably according to the theoretical analysis. The feasibility of the model was verified by experiments and the influence of cutting parameters on the axial force and torque was analyzed. The experiment data had shown that the relative error between the calculated values and the experimental values were within the acceptable range. The axial force and torque increased with the increase in cutting speed and feed rate.